Електропровідність термочутливої склокераміки на основі нанорозмірного діоксиду ванадія - Kolbunov, Vadim; Tonkoshkur, Ilya; Vasheruk, Aleksander (PE "Politekhperiodika", Book and Journal Publishers, 2022)
The metal-semiconductor phase transition (MSPT) in vanadium dioxide is accompanied by an abrupt change in a number of physical parameters of this compound, in particular the resistivity. Of great interest are glass-ceramic materials, which are synthesized on the basis of vanadium dioxide and glass of the V2O5 – P2O5 system. Electronic devices based on such materials can operate at high electric currents. This allows you to create elements known as threshold switches and critical thermistors. This paper presents the results of the study of electrical conductivity and microstructure of thermosensitive glass-ceramics synthesized on the basis of fine crystalline VO2 with crystal sizes of 5–10 μm and on the basis of nanocrystalline VO2 (crystal size 70–100 nm). In general, microstructures are typical for such materials and contain crystals of vanadium dioxide, inclusions of vanadium phosphate glass and other components of glass ceramics. There are also pores in the microstructure of the samples. The temperature dependences of the resistivity for both types of glass-ceramics have a sharp change in the resistivity by 1.5–2 decades in the region of 70°C, which is characteristic of the MSPT in vanadium dioxide. For both types of glass-ceramics, a comparative study of the resistivity during cycling through the phase transition temperature in VO2 was performed. Glass-ceramic samples synthesized on the basis of nanocrystalline VO2 showed much more stable behavior. This allows creating a stable glass-ceramic material for thermistors with a critical temperature of about 70°C.